An Empirical Investigation on Knowledge Workers Productivity in Telecom Sector of Pakistan - Mahmood, Sobia (Information Management and Business Review, 2011)
This study intends to investigate the expectations of knowledge workers from their organization. The firms that understand the expectation of their knowledge workers can more effectively satisfy the needs and increase the productivity of their knowledge workers, which ultimately lead to gaining of competitive advantage. Literature does not depict any research study related to knowledge worker productivity that focuses on Pakistani organization. Hypothesized model consists of organizational culture, reward and technology and their effect on knowledge sharing and finally on knowledge worker productivity. Questionnaire was developed based on rigor method of constructs operationalization, including face, content and reliability. The sample size was 210, which was selected randomly from telecom sector. The data is analyzed by structural equation modeling. The results depicts that if the organization focus on organizational culture, reward and technology, it can achieve highest degree of productivity of knowledge workers. Therefore, the organizations must develop a strong strategy for identification and retention of their knowledge workers. In order to increase the knowledge worker productivity, management required to learn the expectation of knowledge worker from them and organization. Study has significant importance for management in strategic planning, human resource management strategy and retention program.